Validação de método analítico por espectrofotometria UV para sistema emulsionado lipídico contendo benznidazol - Streck, Letícia; Santos, Kátia Solange Cardoso Rodrigues dos; Fernandes-Pedrosa, Matheus de Freitas; Silva-Júnior, Arnóbio Antônio da; Oliveira, Anselmo Gomes de [UNESP] (Sociedade Brasileira de Química, 2011)
A validation study of an UV spectrophotometric method was conducted for quantitative analysis of benznidazol (BZN) in a lipid. The analytical determinations were performed at 315 nm at 25 ºC. The emulsion components did not interfere on drug analyses, demonstrating the specificity of the methodology. A good linearity (r = 0.99995) and precision (RSD < 5.0%) for intra and inter-day studies, including the reproducibility test were observed. The accuracy ranged of 102.1 + 2.8 e 103.8 + 1.7%. The statistical analysis demonstrates a linear, precise, accurate and robust method for BZN quantification from the lipid emulsion system.
Validation of an analytical method by UV spectrophotometry for lipid emulsion system containing benznidazol
Keywords: benznidazol; lipid emulsions; UV-Vis spectrophotometry